An efficient method for analysis of service load stresses in bridge gusset plates. (1st February 2015) - Siekierski, Wojciech
Highlights: Analysis of stresses in bridge gusset plates is possible with a modified beam-element model. In the model: beam elements are used to model truss members while application of shell elements is limited to gusset plates. The model is rather easy to create yet as accurate as regular hybrid model that uses shell elements to model whole structural joint. The above issue is studied in the paper on the basis of results of Author's lab testing of scaled bridge truss girder. Final conclusions include among others a discussion on practical aspects of application of the modified beam-element modelling. Abstract: The paper presents modified beam-element modelling of bridge truss girders. Despite its simplicity the technique provides satisfactory accuracy of assessment of stress distribution in bridge truss gusset plates. The modification consists in the introduction of shell elements modelling gusset plates into a beam-element model of a truss girder. In the paper the modified beam-element modelling of a scaled bridge truss girder is compared to regular hybrid modelling that employs beam elements to model members and shell elements to model joints. The ability of both techniques to predict stress in a gusseted joint of the lab tested scaled girder is investigated. Stresses based on recorded strains and those computed using the described technique are compared. Modified beam-element modelling is shown to be a relatively easy and accurate method for bridge gusset plate analysis.